2013
DOI: 10.1371/journal.pone.0059076
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Diversity of SALMFamide Neuropeptides

Abstract: The SALMFamides are a family of neuropeptides that act as muscle relaxants in echinoderms. Two types of SALMFamides have been identified: L-type (e.g. the starfish neuropeptides S1 and S2) with the C-terminal motif LxFamide (x is variable) and F-type with the C-terminal motif FxFamide. In the sea urchin Strongylocentrotus purpuratus (class Echinoidea) there are two SALMFamide genes, one encoding L-type SALMFamides and a second encoding F-type SALMFamides, but hitherto it was not known if this applies to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…However, these apparent differences in potency may not be physiologically relevant. Recently, it was discovered that in the starfish Patiria miniata, S1 and an S2-like peptide are derived from precursor proteins that comprise 14 other putative SALMFamides (Elphick et al, 2013). Likewise, we have identified neural transcripts encoding the S1 and S2 precursors in A. rubens and have found that the S1 precursor contains six other putative SALMFamides and the S2 precursor contains seven other putative SALMFamides (D.C.S., M.R.P.…”
Section: At 100nmollmentioning
confidence: 89%
“…However, these apparent differences in potency may not be physiologically relevant. Recently, it was discovered that in the starfish Patiria miniata, S1 and an S2-like peptide are derived from precursor proteins that comprise 14 other putative SALMFamides (Elphick et al, 2013). Likewise, we have identified neural transcripts encoding the S1 and S2 precursors in A. rubens and have found that the S1 precursor contains six other putative SALMFamides and the S2 precursor contains seven other putative SALMFamides (D.C.S., M.R.P.…”
Section: At 100nmollmentioning
confidence: 89%
“…The Holothuroidea (sea cucumbers) are a sister group to the class Echinoidea and, as in S. purpuratus , analysis of transcriptome sequence data from A. japonicus revealed two SALMFamide precursor transcripts. One of the precursors comprises three L-type or L-type-like SALMFamides and is homologous to the L-type SALMFamide precursor in S. purpuratus that contains two L-type or L-type-like SALMFamides ( 16 ). The second SALMFamide precursor in A. japonicus is largely comprised of F-type or F-type-like SALMFamides (five in total) but interestingly, unlike the precursor that gives rise to F-type SALMFamides in S. purpuratus , it also contains three L-type/L-type-like SALMFamides ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genome sequence data for the starfish Patiria miniata has been obtained and this has revealed a SALMFamide profile similar to the sea cucumber A. japonicus . Thus, in P. miniata one SALMFamide precursor is solely comprised of L-type SALMFamides, which include S1 and six other structurally related peptides ( 16 ). The other SALMFamide precursor in P. miniata is largely comprised of F-type or F-type-like SALMFamides (eight in total) but it also contains an S2-like peptide with an L-type C-terminal motif ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequenceserver has accelerated our own research (Gotzek et al ., 2011; Ingram et al ., 2012; Wurm et al ., 2011; Wang et al ., 2013; Kulmuni et al ., 2013; Privman et al ., 2013; Mondav et al ., 2014; Schrader et al ., 2014; Nygaard & Wurm, 2015) and that of others. Indeed, despite this being the first formal publication reporting Sequenceserver, the software has already been cited for research on emerging model organisms (Wurm, 2015) such as sea cucumber (Rowe et al ., 2014), starfish (Elphick et al ., 2013; Semmens et al ., 2013, 2015), falcons (Seim et al ., 2015), the sugar-apple tree (Gupta et al ., 2015), the Hessian fly Mayetiola destructor (Shreve et al ., 2013) and the house plant Streptocarpus rexii (Chiara et al ., 2013), as well as for research in bioadhesion (Rodrigues et al ., 2014), environmental microbiology (Castro et al ., 2015), and general research on BLAST (Sharma & Mantri, 2014).…”
Section: Discussionmentioning
confidence: 99%